Running demands and heart rate response in rugby union referees - Suarez-Arrones, L.; Portillo, L. J.; Garcia, J. M.; Calvo-Lluch, A.; Roberts, S. P.; Mendez-Villanueva, A. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to examine the match physical demands and exercise intensity associated with men rugby union refereeing using global positioning system technology. Ten male rugby union referees (age, 37.1 ± 5.9 years; body mass, 83.7 ± 4.8 kg; height, 175.5 ± 6.2 cm) were analyzed 2-4 times during a total of 30 national level matches. The average total distance covered by the referees throughout the game was 6,322.2 ± 564.9 m. As a percentage of total distance, 37.3% (2,356.9 ± 291.3 m) was spent walking, 24.1% (1,524.4 ± 229.4 m) jogging, 10.4% (656.2 ± 130.7 m) running at low intensity, 17.6% (1,110.3 ± 212.2 m) at medium intensity, 5.5% (347.1 ± 27.1 m) at high intensity, and 5.2% (328.1 ± 230.3 m) at sprint. A significant decrease (p < 0.05) in running performance was observed between the first and the second halves in the last 3 speed zones. When the total distance traveled during consecutive 10-minute periods was compared, there was a significantly greater distance covered in the first 10 minutes of the game (876.3 ± 163 m) compared with 50-60 minutes (679.8 ± 117.6 m), 60-70 minutes (713.03 ± 122.3 m), and 70-80 minutes (694.2 ± 125.7 m; all p < 0.05). The average heart rate responses were similar (p > 0.05) in the first (157 ± 7 b/min; 85% HRmax) and second half (155 ± 7 b/min; 84% HRmax). This study provides evidence of reduced high-intensity running toward the end of the game. These findings offer important information to design better training strategies adapted to the requirements and demands of rugby union refereeing.